Vibration isolation of few-layer graphene sheets. (1st March 2020) - Lu, Lu; Ru, C.Q.; Guo, Xingming
Abstract: This work shows that a few-layer graphene with two highly-tensioned outermost layers exhibits negative effective mass and behaves like an elastic metamaterial. Actually, our simulations based on simple elastic membrane model confirm the existence of a bandgap in terahertz range within which a tensioned few-layer graphene exhibits remarkable vibration isolation: forced vibration will be highly restricted to a narrow region around the site of the applied excitation while all other parts of the graphene remain essentially static. The values of terahertz bandgap frequencies are determined by the van der Waals interaction coefficient between adjacent layers, while the width of the bandgap is determined by the number of inner layers. This research may provide new perspectives for designing and analyzing graphene-based metamaterials and nano-resonators with potential applications in high-frequency vibration controlling.